Manual of Otologic Surgery - Arnoldner, Christoph; Lin, Vincent Y.W; Chen, Joseph M. (Springer Vienna : Imprint: Springer, 2015)
Temporal bone dissection training is paramount to the surgical education of any otolaryngologist and a special rite of passage for those who wish to focus their practice on otology. The complexity of temporal bone anatomy, which is exposed in a stepwise fashion during dissection, holds a particular fascination for surgeons at all levels, while mastery of the microsurgical anatomy remains the most basic attribute defining surgical competence and skills. In spite of the recent progress in surgical simulation, the cadaver bone remains the gold standard and provides an indispensable platform for otological training. The Manual of Otologic Surgery takes the reader step-by-step through routine temporal bone surgeries while maximizing the use of the cadaver tissue. In an effort to improve visual realism, the book provides high-resolution photographs and anatomically accurate illustrations to allow the reader to better appreciate the three-dimensional relationship of the internal constructs of the temporal bone. Special emphasis is placed on describing the latest techniques for cochlear implantation and active middle ear implants. The book is further enhanced by additional links to edited videos of surgical cases and will therefore serve as a valuable reference guide to otologic surgeons of all experience levels.